A Linear Regression Analysis Was Conducted To Determine The Principal Dimensions of A Prospective Tourist Ship - Budianto (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
The objective of this research is to design a catamaran tourist ship that incorporates green technology. To achieve this, the main dimensions of the ship will be determined using the linear regression method, based on existing data from similar vessels. The empirical data from existing vessels serves as the foundation for the analysis and prediction, thereby enabling the identification of relationships and patterns between the key variables, including length, width, draft, displacement, and passenger capacity. The linear regression method offers several advantages, including simplicity, ease of interpretation, and efficiency in the use of resources. As a result, it is an effective tool for initial analysis before the application of more complex methods. The R2 value has an average result above 90 percent, so the data can be considered good and valid. The innovative aspect of the design of this tourist ship is the utilisation of data pertaining to existing vessels that have demonstrated optimal performance in their role as tourist ships. The use of existing data not only helps reduce the risk of errors in the design of new vessels but also ensures that the design is efficient and compliant with operational needs and safety regulations. This research confirms the importance of a data-driven approach in the design of environmentally friendly and efficient ships. In the context of ship design and operation, displacement represents a pivotal parameter in linear regression analysis. An understanding of the relationship between displacement and ship performance allows for more accurate predictions regarding speed, fuel consumption, stability, and draft. This allows for the design of ships that are more efficient, stable, and safe, and optimized under a variety of operational conditions.